Transcatheter Closure of Patent Ductus Arteriosus via Different Approaches - Zhou, Zeming; Gu, Yuanrui; Zheng, Hong; Li, Shiguo; Xu, Liang; Liu, Qiong; Wan, Junyi; Lv, Jianhua; Song, Huijun; Yan, Chaowu; Hu, Haibo; Zhang, Gejun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: There have been marked advances in devices such as Amplatzer Duct Occluder II (ADO-II) or vascular plug through 5Fr delivery sheath for closure of patent ductus arteriosus (PDA) in the past five decades, making it possible for cardiologists to deliver occluders via different approaches. However, comparisons of these different approaches have not been reported. Therefore, the aim of this study was to summarize and compare the advantages of different approaches for PDA closure, and to guide clinical strategies. Methods: This retrospective study included all patients undergoing transcatheter closure of PDA from 2019 to 2020. Patients were matched by 1:1 propensity score matching (PSM). The retrograde femoral artery approach (FAA) and simple vein approach (SVA) groups were compared with the conventional arteriovenous approach (CAA). Results: The average age of the 476 patients was 21.05 ± 21.15 years. Their average weight was 38.23 ± 24.1 kg and average height was 130.14 ± 34.45 cm. The mean diameter of the PDA was 4.29 ± 2.25 mm. There were 127 men and 349 women, comprising 205 adults and 271 children. Among them, 197 patients underwent CAA, 223 underwent SVA, and 56 underwent retrograde FAA. The diameter in the FAA group was smaller than that in the other two groups, but was similar in adults and children. In the PSM comparison of CAA and SVA, 136 patients with CAA and 136 patients with SVA were recruited. Simple vein approach was associated with markedly reduced length of hospital stay, length of operation, and contrast medium usage as compared with CAA (all P < 0.05). In the PSM comparison of FAA and CAA, 30 patients with CAA and 30 patients with FAA were recruited. The operation duration was longer in the CAA than in the FAA group. There were no significant differences in postoperative complications among groups. Conclusion: Patent ductus arteriosus closure by using the SVA and FAA is safe and effective, and has certain advantages in some respects as compared with CAA.